V.l.n.r. voor: Jan van Es, Wennekes, Gabriëls. Achter: Van den Berg, Van Es, ?, ?. Origineel in rijksarchief Noord-Brabant
V.l.n.r. voor: Jan van Es, Wennekes, Gabriëls. Achter: Van den Berg, Van Es, ?, ?. Origineel in rijksarchief Noord-Brabant.